2019
DOI: 10.1128/aem.00032-19
|View full text |Cite
|
Sign up to set email alerts
|

Response of Beef Cattle Fecal Microbiota to Grazing on Toxic Tall Fescue

Abstract: Tall fescue, the predominant southeastern United States cool-season forage grass, frequently becomes infected with an ergot alkaloid-producing toxic endophyte, Epichloë coenophialum. Consumption of endophyte-infected fescue results in fescue toxicosis (FT), a condition that lowers beef cow productivity. Limited data on the influence of ergot alkaloids on rumen fermentation profiles or ruminal bacteria that could degrade the ergot alkaloids are available, but how FT influences the grazing bovine fecal microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(68 citation statements)
references
References 89 publications
16
52
0
Order By: Relevance
“…However, the knowledge about a possible involvement of GI tract microbial communities, especially fungal communities, in FT is still highly limited. Recently, Mote et al found in animals fed toxic fescue, relative abundances of the bacterial families Ruminoccocaceae and Lachnospiraceae were significantly increased [17]. Our study predominantly found consistent changes in the fungal OTUs and only detected a single significantly different bacterial OTU (OTU3, Acinetobacter ) within the 50 most abundant OTUs between the tolerance groups, and this OTU was not related to either of the aforementioned families (Fig.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…However, the knowledge about a possible involvement of GI tract microbial communities, especially fungal communities, in FT is still highly limited. Recently, Mote et al found in animals fed toxic fescue, relative abundances of the bacterial families Ruminoccocaceae and Lachnospiraceae were significantly increased [17]. Our study predominantly found consistent changes in the fungal OTUs and only detected a single significantly different bacterial OTU (OTU3, Acinetobacter ) within the 50 most abundant OTUs between the tolerance groups, and this OTU was not related to either of the aforementioned families (Fig.…”
Section: Discussionsupporting
confidence: 48%
“…In general, our knowledge about FT has significantly advanced during recent years [1, 2, 4, 17, 3135]. However, the knowledge about a possible involvement of GI tract microbial communities, especially fungal communities, in FT is still highly limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New data from our lab [ 67 , 68 , 69 ], among other recent reports [ 38 , 70 , 71 ], indicate that developing integrative interactomics-based approaches to complement other, more traditional methods for evaluating the livestock integrome could increase our understanding about the development and adaptive versus pathophysiological responses to one of the costliest diseases to the United States beef industry, fescue toxicosis. The rest of this review will focus on introducing what we currently know about fescue toxicosis development and pathophysiology and how newly generated ‘omics data could be integrated to help fill crucial knowledge gaps related to this disease.…”
Section: Maintaining Animal Productivity and Wellness In Adverse Ementioning
confidence: 99%